An Investigation On The Behaviours Of Buried Structural Arch Culvert With Varying Rise Span Ratio - Liow, Syuk Chin (Universiti Sains Malaysia, 2006)
Since the Romanian Empire until twentieth century, the arch structures are widely applied in all fields of engineering constructions, from bridge, subways, and underground structures to military shelters. The loadings are altered to fulfill the specific demand in transportation systems, materials quantity and the analysis methods. Therefore, we should improvise our understandings on structural behaviour. The behaviour of buried structural arch for span 10m to 30m are analyzed with finite element method. The structural behaviours include the axial force, shear force and bending moment in both distributions diagram and magnitude. By applying three types of load cases, that is self-weight, fill weight and live load, the behaviours of arch for axial force, shear force, bending moment, horizontal and vertical reaction are observed. This research provides a better understanding about the behaviours on buried arch with various rises to span ratio. From the analysis on the behaviours of buried arch by finite element method, the change in arch rise to span ratio for three types of load cases show the increment in maximum axial force, shear force, bending moment, horizontal and vertical reaction. Investigation for buried arch structures with different rise to span ratio is importance for future designs of arch structures, with higher quality, durability and strength. Lastly, future design of arch structures will be able to achieve longer life cycle, cost effectiveness and environmental friendly.